Revisión Sistemática de la Literatura sobre la Efectividad de la Técnica de Restauración Atraumatica en Niños Menores de 10 Años con Difícil Manejo (2023)
Introduction: A therapeutic alternative for treating dental caries is the atraumatic restorative technique (ART), used to treat deep lesions in primary and permanent teeth without pulp symptomatology. The technique does not generate pain and is ideal for anxious or badly behaved patients.